Editorial: latent class analysis to improve confidence in the diagnosis of IBS – authors' reply. Issue 9 (3rd April 2017) - Sood, R.; Gracie, D. J.; Gold, M. J.; To, N.; Pinto‐Sanchez, M. I.; Bercik, P.; Moayyedi, P.; Ford, A. C.; Law, G. R.
Abstract : Linked Content This article is linked to Ballou and Lembo, and Sood et al papers. To view these articles visithttps://doi.org/10.1111/apt.14002 andhttps://doi.org/10.1111/apt.13949 .